EMPATHY IN PRESCHOOL CHILDREN: PSYCHOLOGICAL AND PEDAGOGICAL APPROACHES (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores “Empathy in Preschool Children: Psychological and Pedagogical Approaches.” The research analyzes the psychological mechanisms underlying empathy development, including emotional regulation, theory of mind, imitation, and attachment. Special attention is given to the stages of empathy formation in early childhood. The role of teachers and family cooperation in supporting empathy development is also discussed. The findings show that empathy is a dynamic skill that can be cultivated through consistent psychological support and pedagogical guidance. Preschool represents a sensitive period for empathy formation, making educational interventions particularly effective.